Christian economic ethics history and implications - Finn, Daniel K. 1947- (Minneapolis, Minn. Fortress Press, 2013)
What does the history of Christian views of economic life mean for economic life in the twenty-first century? Here Daniel Finn reviews the insights provided by a large number of texts, from the Bible and the early church, to the Middle Ages and the Protestant Reformation, to treatments of the subject in the last century. Relying on both social science and theology, Finn then turns to the implications of this history for economic life today. Throughout, the book invites the reader to engage the sources and to develop an answer to the volume's basic question.
pt. 1. Introduction. Introduction: well water deep down -- How a living tradition means -- pt. 2. From the Bible to the Reformation. The Hebrew Scriptures -- The New Testament -- The early church -- Christian faith and concern for the poor -- The early church: patristic teaching on ownership and wealth -- The beginnings of monastic life -- The Medieval period: Thomas Aquinas and natural law ethics -- The Medieval period: Thomas Aquinas on four economic issues -- The Protestant Reformation -- pt. 3. Resources for Interpretation. The development of moral teaching -- Engaging controversies today -- What we should and should not learn from economics -- pt. 4. Modern church teaching on economic life. Pope Leo XIII and Pope Pius XI -- Pope John XXIII and Pope Paul VI -- Contemporary Protestant thought on economic life -- Pope John Paul II and Pope Benedict XVI -- pt. 5. Coming to conclusions. Principles for an economic ethic today -- Implications for an economic ethic today -- Society, government, and market: getting the relationships right -- Conclusion
Includes bibliographical references (pages 391-404) and index
Erscheinungsjahr in Vorlageform:[2013]
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Economics -- Religious aspects -- Christianity; Economics -- Moral and ethical aspects; Christian Ethics